2021
DOI: 10.24042/kons.v8i1.7619
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being: The impact of student perceptions on guidance and counseling teachers

Abstract: The increasingly complex problem becomes a challenge for guidance and counselling teachers or counsellors as professional helpers. The ideal guidance and counselling teacher or counsellor figure is expected to answer the challenges of the current millennial era. The objectives to be achieved in this study are to obtain an overview of students' perceptions of the ideal guidance and counselling teacher and to find out the relationship between student perceptions and the level of welfare of Senior High School stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There are many challenges faced by society in today's millennial era, which must be solved by various parties, including counselors. One researcher revealed that the challenge for professional counselors in this millennial and digital era is to increase subjective well-being (Kurniawan et al, 2021). This is in line with the goal of counseling, which is to improve subjective well-being and mental health (Hollingsworth, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are many challenges faced by society in today's millennial era, which must be solved by various parties, including counselors. One researcher revealed that the challenge for professional counselors in this millennial and digital era is to increase subjective well-being (Kurniawan et al, 2021). This is in line with the goal of counseling, which is to improve subjective well-being and mental health (Hollingsworth, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is because many individuals are now busy and fixated on their own personal interests, so concern for the environment is currently running low [7]. This is a challenge for counselors, where the ideal guidance and counselling teacher or counsellor figure is expected to answer the challenges of the current millennial era [8,9].…”
Section: Introductionmentioning
confidence: 99%